2014
DOI: 10.1016/j.jpain.2014.01.498
|View full text |Cite
|
Sign up to set email alerts
|

From Peripheral to Central: The Role of ERK Signaling Pathway in Acupuncture Analgesia

Abstract: Despite accumulating evidence of the clinical effectiveness of acupuncture, its mechanism remains largely unclear. We assume that molecular signaling around the acupuncture needled area is essential for initiating the effect of acupuncture. To determine possible bio-candidates involved in the mechanisms of acupuncture and investigate the role of such bio-candidates in the analgesic effects of acupuncture, we conducted 2 stepwise experiments. First, a genome-wide microarray of the isolated skin layer at the GB3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 66 publications
2
50
0
2
Order By: Relevance
“…2,20 Further studies are necessary to elucidate the mechanism connecting the local and central effects of acupuncture. In addition, acupuncture stimulation results in the local changes of various biological factors, including nitric oxide, 7,8 calcitonin gene-related factor, 9 histamine, 21 phosphorylated extracellular signalregulated kinase, 22 and adenosine triphosphate and its metabolite adenosine. Recently, Goldman et al 23 and Park et al 22 reported that local release or molecular changes such as adenosine or phosphorylated extracellular signal-regulated kinase play an important role in triggering the acupuncture analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…2,20 Further studies are necessary to elucidate the mechanism connecting the local and central effects of acupuncture. In addition, acupuncture stimulation results in the local changes of various biological factors, including nitric oxide, 7,8 calcitonin gene-related factor, 9 histamine, 21 phosphorylated extracellular signalregulated kinase, 22 and adenosine triphosphate and its metabolite adenosine. Recently, Goldman et al 23 and Park et al 22 reported that local release or molecular changes such as adenosine or phosphorylated extracellular signal-regulated kinase play an important role in triggering the acupuncture analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…ERK stimulates the production of Type-1 collagen fibers via transcription factors such as activator protein-1 [115,117]. Interestingly, a recent study by Park et al found that DN at GB34 turned on 236 genes secondary to the ERK cascade [118]. Moreover, blocking the ERK pathway inhibited the anti-nociceptive effects of DN, suggesting that ERK may be the biochemical hallmark of DN analgesia [118].…”
Section: Dry Needling Mechanotransduction and Tissue Healingmentioning
confidence: 99%
“…In addition, improved microcirculation coupled with analgesic effects of needle stimulation could bring about long term improvements. Given the self-reported improvement the patient has experienced, acupuncture may be an option for those suffering from arthritis who wish to reduce their reliance on medication [8][9]. One particular issue of note is that the patient is on Plavix, an anticoagulant prescribed to those who are unable to take aspirin as the standard blood thinner (either due to allergy or contradicting drug interactions), which is listed with the side effect of joint pain, and in some instances, the uncommon side effect of acute osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%